2018
DOI: 10.3390/land7010002
|View full text |Cite
|
Sign up to set email alerts
|

Land Use and Land Cover Changes and Their Effects on the Landscape of Abaya-Chamo Basin, Southern Ethiopia

Abstract: This study uses a combination of remote sensing data, field interviews and observations, and landscape indices to examine the dynamics of land use and land cover (LULC), identify their driving forces, and analyze their effects on the landscape of Abaya-Chamo Basin (ACB) between 1985, 1995, and 2010. The results reveal that the landscape of ACB has changed considerably during the past 25 years between 1985 and 2010. The main changes observed imply a rapid reduction in shrubland (28.82%) and natural grassland (3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
67
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 99 publications
(77 citation statements)
references
References 57 publications
3
67
0
Order By: Relevance
“…The observed (1985 and 2010) LULC dataset used in this study were obtained from Woldeyohannes et al [30], whereas the simulated LULC dataset was created using statistical inference method and Cellular Automata (CA) allocation approaches. As it is briefly indicated in Woldeyohannes et al [30], the observed dataset was generated from Landsat imageries by employing a pixel-based supervised image classification method. Post-classification refinement was applied to enhance the classification accuracy of the final LULC maps.…”
Section: Data Sourcesmentioning
confidence: 99%
See 3 more Smart Citations
“…The observed (1985 and 2010) LULC dataset used in this study were obtained from Woldeyohannes et al [30], whereas the simulated LULC dataset was created using statistical inference method and Cellular Automata (CA) allocation approaches. As it is briefly indicated in Woldeyohannes et al [30], the observed dataset was generated from Landsat imageries by employing a pixel-based supervised image classification method. Post-classification refinement was applied to enhance the classification accuracy of the final LULC maps.…”
Section: Data Sourcesmentioning
confidence: 99%
“…In the past few decades, rapid population growth and rising demand for food in Ethiopia have led to a considerable expansion of cropland at the expense of forest, shrubland/woodlands and grasslands in various part of the country [25][26][27][28][29][30][31]. More than 23 million ha of forest and shrubland/woodlands were cleared since the second half of the twentieth century to make way for agricultural production in the country [32].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Urbanization is generally influenced by national laws, plans, policies and poor governance in many developing countries [9,10]. Population growth increases the demand for natural resources, including land for construction, thus, human disturbances such as pollution, fire, grazing, cutting, and cultivation can also lead to spatial shift in land-use systems [11]. Because of various anthropogenic and natural factors, developing countries experience relatively more rapid urban growth and land-cover changes compared to developed countries [12].…”
Section: Introductionmentioning
confidence: 99%